Durability of wood of Prosopis laevigata and the effect of its extractives on wood-decaying fungus - Carrillo-Parra, Artemio; Hapla, František; Mai, Carsten; Garza-Ocañas, Fortunato (Instituto de Ecología, A.C., 2016)
The natural durability of mezquite wood (Prosopis laevigata) from four localities in Northeast Mexico was determined using two test, a) terrestrial microcosm (European pre-norm 807) during 32 weeks on a non sterilized vertisol soil and, b) laboratory conditions according to the modify European Norm 113, the wood was exposed by 16 weeks to Basidiomycetes Trametes versicolor, Coniophora puteana, Irpex lacteus and Pleurotus ostreatus. The natural durability of two methods were determined by mass loss and by the dynamic modulus of elasticity loss (MOEdyn). Additionally the inhibition effect of wood extracts obtained from wood sawdust in either hot water, ethanol or acetone at 100 parts per million (ppm), 1 000 ppm, 5 000 ppm and 10 000 ppm on growth of C. puteana and T. versicolor was also determined. The results showed that P. laevigata wood from the four sites is similar and very resistant to soil contact; the mass lost was ranging from (9 ± 2)% to (17 ± 5)%. The MOEdin lost of P. laevigata was ranging from (20 ± 4)% to (39 ± 11)%, the control species showed values of (91 ± 13)% and (62 ± 15)% respectively. The second method (modify european norm 113) showed mass loss of P. laevigata for the four localities and the four fungi ranging from (0,7 ± 0,5)% to (2,6 ± 3,2)%, placed this species as a class 1 (i.e. very durable) according to the European Norm 350-1. The MOEdyn losses was from (3,8 ± 4,2)% to (19,9 ± 5,6)%. The hot water extracts at 1 0000 ppm concentration inhibited growth of C. puteana and T. versicolor by (83 ± 8)% and (93 ± 6)% respectively.